Enhancement of activity and lifetime of nano-iron oxide catalyst for environmentally friendly catalytic phenol oxidation process - Khaleel I. Hamad; Jasim I. Humadi; Yousif S. Issa; Saba A. Gheni; Mustafa A. Ahmed; Ahmed A. Hassan (Cleaner Engineering and Technology, 2022)
The amount and characteristics of wastewater produced are determined by the process configuration. Refineries produce contaminated effluent of phenol levels up to 300–600 mg/L. For wet oxidation of phenol, multiloading and multifunctional MnO2/Fe2O3 were utilized in the present study to develop a cost-effective nanocatalyst to clean refinery wastewater at a high rate of phenol removal and a long lifetime of catalyst activity. The catalysts were doped with two different loading of 2% and 5% of MnO2. For full oxidation of carcinogenic phenolic compounds into the unharmful CO2 and H2O, the catalytic breakdown of H2O2 as an oxidation agent produces oxygen bubbles and hydroxyl radicals. The prepared catalysts were evaluated in a batch reactor and the results showed that the loading of MnO2 over the Fe2O3 has a positive impact on the oxidation of phenol as increasing the MnO2 loading increased the rate of phenol oxidation and did not result in the deactivation of the available catalyst pores. The highest conversion of phenol achieved was 94 wt% at 80 min and 75 °C over the 5% MnO2/Fe2O3 catalyst. Also, it was observed that the prepared catalyst sustained the deactivation for several cycles of catalytic oxidation of phenol as the catalyst activity remained almost constant as time proceeds to 120 min.